Pengaruh Media Pembelajaran Al-Qur’an Berbasis Multimedia Terhadap Minat Belajar Al-Qur’an - Sri Siswanti, Muhammad Fathoni, Didik Nugroho (Jurnal Ilmiah SINUS, 2013)
The purpose of the research is to create a tutorial that can be used as a tool in the process of learning to read the Quran with correct spelling and appropriate, provide alternative instruction on how to learn to read the Quran by utilizing computer media and facilitate the beginners do learning to read the Quran on their own. Methods of data collection using interviews, observations, and questionnaires. Results of research in the know that the percentage of students in terms of interest in the material presented is very good value is 86% while 14% is good and bad is 0%, and the percentage in the spirit of understanding the material from the questionnaire were very good value 27% , a good 73% while that is not good is 0%. The final conclusion of the use of multimedia based learning media is that the media has a positive influence on learning Al-Quran for children landfill. While the aspect of students with learning ninat implementation multimedia media-based learning is an increase of 20% from the original 40 students widened 50 students Â Keyword: Al-Qur’an, Multimedia, Learning, interest